1976
DOI: 10.2307/2053271
|View full text |Cite
|
Sign up to set email alerts
|

A Model for the Study of Thai Buddhism

Abstract: THIS paper constitutes an attempt to reconcile—at least for one region of Southeast Asia: central Thailand—one of the discrepancies in analyses of contemporary Theravada Buddhism. The model proposed below—which is the outcome of comparing some of the relevant literature with my own field data—encompasses two distinct sections of society, each holding a different attitude towards Buddhism. The interaction between different interpretations of religion may well be one of the major factors n i the process of relig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Moreover, merit making, another important Buddhist concept, encourages participation in such religious activities as temple visit, alms offering, and/or becoming a Buddhist monk (for boys). Not only is merit making an indication of commitment to the Buddhist way of life but also a means to overcome "bad" karma [18,19,24]. Finally, the Buddhist principles and teachings are known for promoting compassion, kindness, hope, and optimism [25], albeit in such terms as suffering, which can by exemplified in the Four Noble Truths: "life is filled with suffering; the source of suffering is craving; suffering ends when craving ceases; and the way to end suffering and craving is the eight-fold path" [26].…”
Section: Buddhism and Mental Healthmentioning
confidence: 99%
“…Moreover, merit making, another important Buddhist concept, encourages participation in such religious activities as temple visit, alms offering, and/or becoming a Buddhist monk (for boys). Not only is merit making an indication of commitment to the Buddhist way of life but also a means to overcome "bad" karma [18,19,24]. Finally, the Buddhist principles and teachings are known for promoting compassion, kindness, hope, and optimism [25], albeit in such terms as suffering, which can by exemplified in the Four Noble Truths: "life is filled with suffering; the source of suffering is craving; suffering ends when craving ceases; and the way to end suffering and craving is the eight-fold path" [26].…”
Section: Buddhism and Mental Healthmentioning
confidence: 99%
“…Despite some strong insistences from official authorities -the Sangha, the elite and the intellectuals -that Buddhist teachings and principles outlined in the Tripitaka are authentic essences and institutionalised forms of the religion, its popular version has been perceived and interpreted otherwise. The syncretic elements of Thai Buddhism comprise what scholars regard as Theravada Buddhism, folk Brahmanism, and pre-Buddhist indigenous animism (Anuman, 1961;1986;Kirsch, 1967;1977;Terwiel, 1976;1979). Religious syncretism and complexity have formed the religious lifelines of the Thais for centuries, as they have been well tolerated and blended into a multi-layered harmonious religious system.…”
Section: Thailand's Syncretic Buddhism and Popular Religiosity In Thementioning
confidence: 99%
“…This phenomenon is noted by many scholars, Ames (1964) stated that magic and religion cannot be distinguished empirically because they are actually compounded. Terwiel (1976) noted that Buddhist and non-Buddhist elements have become so intermingled it is impossible to draw a distinction between them. Rajadhon (1988) also suggested that there are two strata of beliefs of the Thai people: animism and Buddhism.…”
Section: Introductionmentioning
confidence: 99%